2016
DOI: 10.1021/acs.molpharmaceut.6b00391
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Lauryl Sulfate Competitively Interacts with HPMC-AS and Consequently Reduces Oral Bioavailability of Posaconazole/HPMC-AS Amorphous Solid Dispersion

Abstract: Sodium lauryl sulfate (SLS), as an effective surfactant, is often used as a solubilizer and/or wetting agent in various dosage forms for the purpose of improving the solubility and dissolution of lipophilic, poorly water-soluble drugs. This study aims to understand the impact of SLS on the solution behavior and bioavailability of hypromellose acetate succinate (HPMC-AS)-based posaconazole (PSZ) ASDs, and to identify the underlying mechanisms governing the optimal oral bioavailability of ASDs when surfactants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…In these particles, polymers were able to inhibit crystallization (Ueda et al, 2017). Similar results were demonstrated in a study of a posaconazole-HPMC-AS system (Chen et al, 2016b).…”
Section: Api In Amorphous-liquid Phase Separationsupporting
confidence: 81%
“…In these particles, polymers were able to inhibit crystallization (Ueda et al, 2017). Similar results were demonstrated in a study of a posaconazole-HPMC-AS system (Chen et al, 2016b).…”
Section: Api In Amorphous-liquid Phase Separationsupporting
confidence: 81%
“…10,13 Drug-polymer interaction also plays an important role during the dissolution process of ASDs. 19,23,24 Therefore, the molecular interaction between BMS-817399 and PVP was firstly studied using FT-IR.…”
Section: Specific Drug-polymer Interactions Studied By Ft-irmentioning
confidence: 99%
“…Moreover, the presence of a surfactant in the ASD formulation could increase wettability of the relatively hydrophobic drug [17,18], while it can also inhibit drug precipitation in the aqueous medium [19,20]. On the contrary, other studies [21][22][23][24] have suggested that surfactants negatively affected drug release from ASDs due to the competitive interaction between the drug-polymer-surfactant, resulting in drug recrystallization promotion from the supersaturated solutions. Therefore, to say the least, the impact and roles of surfactants in the dissolution of drug ASDs are complex and somewhat elusive, and the use of surfactants can be detrimental or beneficial depending on the specific drug-polymer-surfactant system and composition.…”
Section: Introductionmentioning
confidence: 99%